ANALISIS PENGEMBANGAN KARIR ASN YANG TERDAMPAK PERAMPINGAN BIROKRASI TERHADAP KEBIJAKAN PENYETARAAN JABATAN STUKTURAL DI PEMERINTAH PROVINSI SUMATERA BARAT - Elfira Sari Roza; Yulihasri; Laura Syahrul (Journal Publicuho, 2024)
This research aims to determine the career development of ASNs who are affected by the equalization of Structural Positions in the government of West Sumatra Province. The type of research used was qualitative research conducted on ASN Government of West Sumatra Province. This research was carried out by selecting 8 informants who were affected by the Bureaucratic Streamlining policy in the West Sumatra Provincial Government. The data collection technique used in this research was in-depth interviews with informants. The research results show that the career development of ASNs affected by bureaucratic downsizing is the same as Functional ASNs. However, there are obstacles in career development because there are position maps for ASN that are not appropriate and do not have work items in the work organization. This has an impact on ASN's career, causing them to be unable to obtain credit points for promotion and their career stalls until retirement.